Pengaruh Financing to Deposit Ratio, Capital Adequacy Ratio, dan Operating Cost Ratio terhadap Manajemen Laba di Perbankan Syariah - Iis Putri Astuti; Jasman Jasman (Akuntabilitas, 2022)
This study aims to examine the impact of financing to deposit ratio (FDR), capital adequacy ratio (CAR), and operating cost ratio (BOPO) on earnings management in islamic banks for the period 2014-2019. There are eight islamic banks as the research sample through purposive sampling method. The data used was the annual report data obtained from the official website of each bank. The data analysis technique used was multiple linear regression. The results of the study showed that financing to deposit ratio has no effect on earnings management, capital adequacy ratio has a significant and positive effect on earnings management, and operating cost ratio has a significant and positive effect on earnings management. These results provide empirical evidence that there are earnings management practices in islamic banks.